Towards an environmental accounting framework for the EU - Anton Steurer (Fondazione Eni Enrico Mattei (FEEM), 2000)
This paper describes work on environmental accounts at Eurostat. Areas of work include asset accounts for forests, subsoil resources, land and water; NAMEA emission accounts; economy-wide material flow accounts; accounts for environmental expenditure and taxes, environment industry and employment; and monetary valuation. For each area of work the present state, future development and numerical findings are presented. The paper concludes that in several environmental accounts areas frameworks and methods have been developed and their applicability demonstrated in practice. For these, future work will focus on systematic implementation in Member States allowing regular compilation of numerical results at lower costs. For less mature areas research and experimental applications will continue. This includes monetary valuation of environmental functions and derivation of 'adjusted' national accounts aggregates.
Keywords: Q2; Q3; O47; 330; Green national accounting; environmental accounting in official statistics; Umweltökonomische Gesamtrechnung; Statistisches Amt; EU-Staaten